Transcriptomic Analysis of Vibrio parahaemolyticus Reveals Different Virulence Gene Expression in Response to Benzyl Isothiocyanate - Song, Jie; Hou, Hong-Man; Wu, Hong-Yan; Li, Ke-Xin; Wang, Yan; Zhou, Qian-Qian; Zhang, Gong-Liang (Molecules, 2019)
Vibrio parahaemolyticus isolated from seafood is a pathogenic microorganism that leads to several acute diseases that are harmful to our health and is frequently transmitted by food. Therefore, there is an urgent need for the control and suppression of this pathogen. In this paper, transcriptional analysis was used to determine the effect of treatment with benzyl isothiocyanate (BITC) extracted from cruciferous vegetables on V. parahaemolyticus and to elucidate the molecular mechanisms underlying the response to BITC. Treatment with BITC resulted in 332 differentially expressed genes, among which 137 genes were downregulated, while 195 genes were upregulated. Moreover, six differentially expressed genes (DEGs) in RNA sequencing studies were further verified by quantitative real-time polymerase chain reaction (qRT-PCR). Genes found to regulate virulence encoded an l-threonine 3-dehydrogenase, a GGDEF family protein, the outer membrane protein OmpV, a flagellum-specific adenosine triphosphate synthase, TolQ protein and VirK protein. Hence, the results allow us to speculate that BITC may be an effective control strategy for inhibiting microorganisms growing in foods.